KERUSAKAN MORFOLOGI TUMBUHAN KOLEKSI KEBUN RAYA PURWODADI OLEH BENALU (LORANTHACEAE DAN VISCACEAE) - Sunaryo, Sunaryo; Rachman, Erlin; Uji, Tahan (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Purwodadi Botanic Gardens-LIPI (The Indonesian Institute of Sciences), East Java, is an ex-situ conservation area accommodating various living plant collections.Identification of the parasitic plants conducted in August 200S found five species parasiting 10S trees belonging to SI species of 24 genera. The highest parasite frequency was found on Ficus (Moraceae). The mistletoes found in the study area were Dendrophthoe pentandra (L.) Miq. (Loranthaceae), Macrosolen tetragonus (Bl.) Miq. (Loranthaceae),Scurrula atropurpurea (Bl.) Dans. (Loranthaceae), Viscum articulation Burm. f. (Viscaceae), and Viscum ovalifolium DC. (Viscaceae).The damaging effect of the parasitic mistletoes generally occurred on the distal part of branches or twigs of the host tree species.